Ion Channels - Fermini, Bernard; Priest, Birgit; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
Ion channels play a vital role in basic physiological functions such as generation of electrical activity in nerves and muscle, control of cardiac excitability, intracellular signaling, hormone secretion, cell proliferation and many other biological processes. Because of their prevalence and the critical role they play in virtually all tissue types and organs, ion channels are also involved in a number of pathophysiological conditions. The aim of this volume is to review recent advances in the field of ion channel related diseases. Following an overview chapter summarizing the current state of ion channel screening technologies, five topics covering areas such as cancer, cardiac arrhythmias, cystic fibrosis, and pain have been selected, and the current state of knowledge is presented by leading experts in their field. Each chapter is structured to cover the biological rationale for the target, the current status in the development of agents to treat the disease, and future prospects and challenges facing each therapeutic area. The reader will receive a critical overview covering the progress made in the rapidly developing and complex field of ion channels and diseases.
Recent Advances in Ion Channel Screening Technologies -- Role of Kv7 and Cav3 Ion Channels in Pain -- Potassium Channels: Oncogenic Potential and Therapeutic Target for Cancers -- Pharmacological Rescue of Mutant CFTR Function for the Treatment of Cystic Fibrosis -- On the Process of Finding Novel and Selective Sodium Channel Blockers for the Treatment of Diseases -- Kv1.5 Potassium Channel Inhibitors for the Treatment and Prevention of Atrial Fibrillation.
Keywords: Medicinal chemistry; Pharmacology; Organic chemistry; Molecular biology; Medicinal Chemistry; Pharmacology/Toxicology.; Organic Chemistry; Molecular Medicine